2000
DOI: 10.1007/bf02682103
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the hemopoietic system of mice deficient for tumor necrosis factor or lymphotoxin-α

Abstract: Hemopoietic and stromal precursor cells were studied in mice deficient for tumor necrosis factor or lymphotoxin-alpha. In normal hemopoiesis the main characteristics of hemopoiesis in knockout mice did not differ from those in wild-type mice. Implantation of bone marrow cells from mice deficient for tumor necrosis factor onto irradiated sublayer of a long-living bone marrow culture led to a notable increase in the number of mature cells and granulocytic-macrophage precursor cells. This can be due to the fact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This was further supported in vitro in TNF-deficient long-term bone marrow cultures, which were characterized by increased proliferative potential of granulocytic progenitors and increased numbers of CFU-GMs within sorted LSK population, as compared to WT BM cultures ( 19 ). Consistent with in vitro data, CFU-GM formation was reduced in WT-recipient mice reconstituted with TNF-deficient BM, suggesting a possible role of TNF, expressed by hematopoietic and not by stromal cells, in inducing cell death at the GMP stage ( 33 ). This is also in agreement with data showing elimination of GMPs by TNF in a dose-dependent manner ( 21 ).…”
Section: Tnf In Stress- and Inflammation-induced Hematopoiesissupporting
confidence: 81%
“…This was further supported in vitro in TNF-deficient long-term bone marrow cultures, which were characterized by increased proliferative potential of granulocytic progenitors and increased numbers of CFU-GMs within sorted LSK population, as compared to WT BM cultures ( 19 ). Consistent with in vitro data, CFU-GM formation was reduced in WT-recipient mice reconstituted with TNF-deficient BM, suggesting a possible role of TNF, expressed by hematopoietic and not by stromal cells, in inducing cell death at the GMP stage ( 33 ). This is also in agreement with data showing elimination of GMPs by TNF in a dose-dependent manner ( 21 ).…”
Section: Tnf In Stress- and Inflammation-induced Hematopoiesissupporting
confidence: 81%
“…The incidence of hemopoietic precursor cells was evaluated by the count of cells forming cobblestone areas on days 7 and 28 (CAFC-7 and CAFC-28) as described previously [5], the count of granulocytic macrophagal CFU (CFU-GM) was determined by a previously described method [4], and the incidence of splenic CFU (CFU-S) by the method of Till and MacCulloch [1]. In order to evaluate the self-maintenance capacity of stromal cells released after long culturing into TNF-/-LTBMC suspension fraction, the cells of this fraction from the test cultures were inoculated into a 24-well plate (100,000 cells per well) for culturing in Fisher medium with 15% FCS and 10% WEHI 3B cell strain conditioned medium.…”
Section: Methodsmentioning
confidence: 99%
“…The functional in vitro tests showed that interaction between stromal and hemopoietic cells is disturbed in knockout mice: stromal precursor cells of mice deficient for TNF (TNF-/-mice) practically do not tolerate the microenvironment during ectopic bone marrow transplantation [1].…”
mentioning
confidence: 99%